Hydrophobic affinity chromatography of nucleic acids and proteins. - Cashion, P (1980)
5' tritylated oligonucleotides binding hydrophobically to low trityl cellulose/sepharose (< 15 microMTr/ml) retain their hydrogen-bonding specificities for complementary sequences. This, constitutes a novel mode of attaching affinity ligands to solid supports, is more convenient than existing methods, and proceeds with 100% yield. The salt, dielectric constant and temperature dependence of these non-covalently anchored ligands permits the isolation of a variety of RNAs including fibroin mRNA. Medium trityl sepharose (15-40 microM Tr/ml) has a high binding specificity for poly A and poly A containing mRNA, equivalent to dT cellulose. Most proteins, including nucleic acid enzymes, bind to these columns and retain enzymatic activity, thus mimicking enzymes attached covalently to solid phases. A number of in vivo counterparts to this hydrophobically determined specificity are noted, as are homologies to nitro-cellulose filters.